Styx y Stygius como designaciones del infierno y de lo infernal - Luque Moreno, Jesús (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
The noun Styx and its derivative adjective Stigius, which refer to one of the waters after death, are forms essentially poetic, as poetic is the idea they convey. Quite early in time, they were also used to make reference not only to those specific waters, but to the world beyond and to hell in general, where they were located.